2018
DOI: 10.1016/j.prevetmed.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of pseudorabies in intensive pig farms in Shanghai, China: Herd-level prevalence and risk factors

Abstract: Pseudorabies (PR), also known as Aujeszky's disease, is a highly contagious disease affecting pigs and a wide range of animals. Pseudorabies is enzootic in many countries. In China, it is a priority animal disease for control and eradication, however the data on disease frequency in intensive pig farms and the information on associated risk factors is inadequate. A cross-sectional study of intensive pig farms (≥350 sows) in Shanghai was conducted to determine herd-level prevalence of PRV and associated risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
2
11
0
2
Order By: Relevance
“…In this study, 18,815 serum samples of pigs in different production phases were collected from pig farms in eight investigated cities in Heilongjiang province, and were subsequently examined by ELISA on an annual basis to investigate gB-and gE-specific antibody level and SPR. Consistent with results of previous publications (7,14,19,21), >80% of pigs were vaccinated in the investigated farms in Heilongjiang province, according to the higher level of PRV gB SPR rates described in Table 1 from 2013 to 2018. Moreover, S/N ratio of different investigated herds showed lower than 0.6, ranging from 0.17 to 0.54.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, 18,815 serum samples of pigs in different production phases were collected from pig farms in eight investigated cities in Heilongjiang province, and were subsequently examined by ELISA on an annual basis to investigate gB-and gE-specific antibody level and SPR. Consistent with results of previous publications (7,14,19,21), >80% of pigs were vaccinated in the investigated farms in Heilongjiang province, according to the higher level of PRV gB SPR rates described in Table 1 from 2013 to 2018. Moreover, S/N ratio of different investigated herds showed lower than 0.6, ranging from 0.17 to 0.54.…”
Section: Discussionsupporting
confidence: 91%
“…An investigation of the prevalence of PRV is required to build up strategies to control and even eradicate PR and minimize the risk of humans contacting this infectious pathogen. Though the prevalence and genetic characteristics of PRV have been documented in several regions or provinces of China [ 2 , 3 , 10 , 11 ], the relevant information in Yunnan Province in recent years is still not available. To fill in this gap, 20,158 pig serum samples were collected from 2017 to 2021 to investigate the epidemiology of PRV in Yunnan Province.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 18,815 serum samples of pigs in different production phases were collected from pig farms in eight investigated cities in Heilongjiang province, and were subsequently examined by ELISA on an annual basis to investigate gB-and gE-specific antibody level and sero-prevalence rate (SPR).Consistent with results of previous publications [10,[13][14][15], more than80% of pigs were vaccinated in the investigated farms in Heilongjiang province, according to the higher level of PRV-gB SPR rates described in Table 1 (Table 4). Previous studies conducted in Shandong province in China have shown that a high proportion of pigs were latently infected by PRV in the investigated region [16,17], which was recognized to be the most critical source of infection when the latent viral genome is reactivated [5].…”
Section: Discussionmentioning
confidence: 59%